Cigarette Smoke Initiates Oxidative Stress-Induced Cellular Phenotypic Modulation Leading to Cerebral Aneurysm Pathogenesis. Issue 3 (March 2018) - Starke, Robert M.; Thompson, John W.; Ali, Muhammad S.; Pascale, Crissey L.; Martinez Lege, Alejandra; Ding, Dale; Chalouhi, Nohra; Hasan, David M.; Jabbour, Pascal; Owens, Gary K.; Toborek, Michal; Hare, Joshua M.; et al.
Abstract : Objective—: Cigarette smoke exposure (CSE) is a risk factor for cerebral aneurysm (CA) formation, but the molecular mechanisms are unclear. Although CSE is known to contribute to excess reactive oxygen species generation, the role of oxidative stress on vascular smooth muscle cell (VSMC) phenotypic modulation and pathogenesis of CAs is unknown. The goal of this study was to investigate whether CSE activates a NOX (NADPH oxidase)-dependent pathway leading to VSMC phenotypic modulation and CA formation and rupture. Approach and Results—: In cultured cerebral VSMCs, CSE increased expression of NOX1 and reactive oxygen species which preceded upregulation of proinflammatory/matrix remodeling genes (MCP-1, MMPs [matrix metalloproteinase], TNF-α, IL-1β, NF-κB, KLF4 [Kruppel-like factor 4]) and downregulation of contractile genes (SM-α-actin [smooth muscle α actin], SM-22α [smooth muscle 22α], SM-MHC [smooth muscle myosin heavy chain]) and myocardin. Inhibition of reactive oxygen species production and knockdown of NOX1 with siRNA or antisense decreased CSE-induced upregulation of NOX1 and inflammatory genes and downregulation of VSMC contractile genes and myocardin. p47phox −/− NOX knockout mice, or pretreatment with the NOX inhibitor, apocynin, significantly decreased CA formation and rupture compared with controls. NOX1 protein and mRNA expression were similar in p47phox −/− mice and those pretreated with apocynin but were elevated in unruptured and ruptured CAs. CSE increased CA formation and rupture, which was diminished with apocynin pretreatment. Similarly, NOX1 protein and mRNA and reactive oxygen species were elevated by CSE, and in unruptured and ruptured CAs. Conclusions—: CSE initiates oxidative stress-induced phenotypic modulation of VSMCs and CA formation and rupture. These molecular changes implicate oxidative stress in the pathogenesis of CAs and may provide a potential target for future therapeutic strategies. Abstract : Supplemental Digital Content is available in the text.